Pengetahuan Guru Vokasi dalam Pembelajaran Berbasis Produksi: Studi Sosio Kulturral pada Immplementasi Teaching Factory di SMK - Dedi Purwanto; Agus Pramono; Siswo Wardoyo (VOCATECH: Vocational Education and Technology Journal, 2026)
AbstractTeaching Factory (TEFA) is increasingly recognized as a strategic approach in vocational education for linking school learning with authentic industrial practices through production-based learning. However, limited research has examined how TEFA shapes the professional knowledge of vocational teachers. This study aims to explore and characterize the knowledge developed by vocational teachers involved in TEFA implementation in vocational high schools (SMK), using a socio-cultural perspective within the framework of Technical and Vocational Education and Training (TVET). An exploratory qualitative design was employed using a repeated concept mapping method. The study involved 18 experienced vocational teachers from three different fields of expertise who had consistently implemented TEFA. Data analysis distinguished between the content and characteristics of teachers’ knowledge. The knowledge content was categorized into six main components, while its characteristics were examined in terms of concreteness, complexity, specificity, and breadth. The findings indicate that teachers’ knowledge in the TEFA context primarily focuses on occupational competence and the management of production-based learning processes. This knowledge demonstrates high levels of concreteness and complexity due to its close connection with real workplace practices and the integration of pedagogical, occupational, and organizational dimensions. Conversely, knowledge related to students and teacher professional development appears less explicitly articulated. The study concludes that TEFA shapes vocational teachers’ knowledge as a situated and knowledge-intensive professional practice.     Keywords:Teaching Factory, Vocational Teacher Knowledge, Technical and Vocational Education and Training (TVET), Socio-Cultural Perspective, Vocational High School. AbstrakTeaching Factory (TEFA) semakin diakui sebagai pendekatan strategis dalam pendidikan vokasi untuk menghubungkan pembelajaran di sekolah dengan praktik industri yang autentik melalui kegiatan pembelajaran berbasis produksi. Namun, penelitian yang mengkaji bagaimana TEFA membentuk pengetahuan profesional guru vokasi masih terbatas. Penelitian ini bertujuan untuk mengeksplorasi dan mengkarakterisasi pengetahuan yang dikembangkan oleh guru vokasi yang terlibat dalam implementasi TEFA di Sekolah Menengah Kejuruan (SMK), dengan menggunakan perspektif sosio-kultural dalam kerangka Technical and Vocational Education and Training (TVET). Penelitian ini menggunakan desain kualitatif eksploratif dengan metode concept mapping berulang. Sebanyak 18 guru vokasi berpengalaman dari tiga bidang keahlian yang secara konsisten menerapkan TEFA terlibat dalam penelitian ini. Analisis data berfokus pada pembedaan antara isi dan karakteristik pengetahuan guru. Isi pengetahuan dikategorikan ke dalam enam komponen utama, sedangkan karakteristiknya dianalisis berdasarkan tingkat kekonkretan, kompleksitas, spesifisitas, dan keluasan. Hasil penelitian menunjukkan bahwa pengetahuan guru dalam konteks TEFA terutama berfokus pada kompetensi okupasional dan pengelolaan proses pembelajaran berbasis produksi. Pengetahuan ini menunjukkan tingkat kekonkretan dan kompleksitas yang tinggi karena berkaitan erat dengan praktik kerja nyata serta mengintegrasikan dimensi pedagogis, okupasional, dan organisasional. Sebaliknya, pengetahuan yang berkaitan dengan peserta didik dan pengembangan profesional guru cenderung kurang terungkap secara eksplisit. Penelitian ini menyimpulkan bahwa TEFA membentuk pengetahuan guru vokasi sebagai praktik profesional yang bersifat kontekstual dan intensif pengetahuan. Kata Kunci:            Teaching Factory, Pengetahuan Guru Vokasi, Pendidikan dan Pelatihan Vokasi (TVET), Perspektif Sosio-Kultural, Sekolah Menengah Kejuruan.